Urgensi Pemenuhan Jaminan Hak Pendidikan Dan Kesehatan Sebagai Hak Asasi Manusia Terhadap Anak Didik Pemasyarakatan - Faris Abiyyu Ramadhan; Padmono Wibowo (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research employs a qualitative method to explore the urgency of fulfilling the rights to education and health as human rights for juvenile inmates. The study focuses on an in-depth analysis of the fulfillment of these rights based on prevailing legal norms. Data is obtained through literature review and in-depth interviews with relevant stakeholders. The findings highlight the high urgency of meeting the rights to education and health for juvenile inmates within the framework of human rights. Despite legal regulations addressing these rights, their implementation faces challenges such as limited study time, insufficient nutrition, and irregular health check-ups. Utilizing qualitative methods, this research contributes to a profound understanding of these issues and connects them to legal norms. The research findings aim to provide a foundation for improving policies and implementing more effective juvenile correctional programs. Additionally, it seeks to promote the human rights of children within the context of the criminal justice system